Inventions of scientists, engineers and specialists from different countries in the area of nanotechnologies. Part V - Leonid A. Ivanov (OOO "CNT «NanoStroitelstvo», 2021)
Introduction. Advanced technologies impress people’s imagination demonstrating the latest achievements (materials, methods, systems, technologies, devices etc.) that dramatically change the world. This, first of all, concerns nanotechnological inventions designed by scientists, engineers and specialists from different countries. Main part. The article provides an abstract overview of inventions of scientists, engineers and specialists from different countries: Russia, USA, China, Belarus, Italy. The results of the creative activity of scientists, engineers and specialists, including inventions in the field of nanotechnology and nanomaterials allow, when introduced to industry, achieving a significant effect in construction, housing and communal services, and related sectors of the economy. For example, the invention «Protective coating and method of its application» relates to the field of protecting metals from corrosion. To obtain a protective coating, a composition containing an industrial oil with a powder of a phosphorusmodified copper-carbon nanocomposite is applied to the surface of an unalloyed steel and subjected to thermochemical activation by heating for 20 minutes at a temperature of 100–200°C. During the formation of the coating, strong donor-acceptor bonds of iron atoms with phosphorus, which are in the composition of the copper-carbon nanocomposite, are formed. In the course of experiments, it was found that heating samples with a coating of oil with the addition of a phosphorus-modified copper-carbon nanocomposite to 100–200°C increases the chemical activity of the nanocomposite, as a result of which a protective coating forms on the surface, which reduces the corrosion rate depending on the concentration of the modified metal-carbon nanocomposite. by 70–95%. The following inventions in the field of nanotechnology are also of interest to specialists: a method for obtaining a nanostructured surface of a metal workpiece by laser treatment, a device for producing nanodispersed metal oxides, a method for producing a nanostructured composite material based on aluminum, a method for modifying the surfaces of plates of a brazed plate heat exchanger, etc. Conclusion. One of the most challenging tasks the economy of every country face is to increase industrial competitiveness through technological upgrade. From the side of the state and companies the principal object to control in this process are the people and enterprises dealing with introduction of inventions and new technologies.